An ACTH-activated protein tyrosine phosphatase (PTP) is modulated by PKA-mediated phosphorylation - Paz, Cristina del Valle (2000)
In adrenal cortex, ACTH regulation of steroidogenesis depends on PKA-dependent serine/threonine phosphorylation and also on the activity of protein tyrosine phosphatases (PTPs). In addition, ACTH increases total PTPs involving at least three soluble PTPs (50, 82 and 115 kDa). Serine/threonine phosphorylation of these enzymes themselves could be a regulatory mechanism of their activity since the increase of total PTP activity is dependent on PKA-activation. In this report we analyzed the effect of in vitro phospho-dephosphorylation processes on the activity displayed by the ACTH-activated PTP of 115 kDa. Using an in-gel PTP assay we demonstrate that dephosphorylation catalyzed by potato acid phosphatase (PAP) reduces the activity of the 115 kDa PTP present in ZF from ACTH-treated animals and PKA-mediated phosphorylation reverses this effect.